Risk-based contracting for high-need Medicaid beneficiaries: The Arkansas PASSE program - Adrienne Nevola; Michael E. Morris; Carrie Colla; J.Mick Tilford (Elsevier, 2021)
The high cost of health care for people with behavioral health (BH) conditions or intellectual and developmental disabilities (IDD) in the United States led one state to implement the Provider-led Arkansas Shared Savings Entity (PASSE) program. PASSE is a managed care model that puts provider-led organizations at risk for the highest need people with BH conditions or IDD in Medicaid, a public health insurance program for low-income residents. Drawing on key informant interviews and payment models across the United States, we describe the PASSE program, how it compares with state Medicaid programs for similar populations, and prospects for the program. Key informants cited several PASSE features as promising mechanisms to improve beneficiary outcomes: expanded care coordination, service flexibility, incentives for community investments, accountability for cost and quality across physical health, behavioral health, and long-term care, quality target accountability, fostered competition, and provider ownership. Informants worry that PASSE features will be insufficient to catalyze changes in provider behavior. Efforts may be targeted to control costs primarily through service reductions with uncertain effects on quality of care. PASSE hinges on improved care coordination and increased efforts to address social determinants of health. Success or failure in these areas will likely determine whether PASSE leads to improved outcomes for two of the most costly and vulnerable populations.